Do pre-existing medical conditions affect COVID-19 incidence and fatality in Nigeria? A Geographical Perspective - Osayomi Tolulope; Adeleke Richard; Yaya Sanni; Ayanda Joy Temitope; Akpoterai Lawrence Enejeta; Fatayo Opeyemi Caleb (Open Health, 2022)
Clinical evidence shows the incidence of novel coronavirus is associated with pre-existing medical conditions. Thus, people with pre-existing medical conditions are more likely to be infected with COVID-19. In light of this, this paper examined the extent to which pre-existing medical conditions are related to COVID-19 incidence and mortality in Nigeria from a geographical perspective. We used the geographically weighted regression (GWR) to determine the effect and extent to which pre-existing medical conditions affect COVID-19 incidence in Nigeria. Our findings show that besides the remarkable spatial variation in COVID-19 incidence and mortality, obesity was a significant predictor of COVID-19 with its effect strongest in southwest Nigeria and other parts of the country. The conclusion of the paper is that areas with high prevalence of pre-existing medical conditions coincide with areas with high COVID-19 incidence and fatality. We recommended that there should be a spatially explicit intervention on the reduction of exposure to COVID-19 among states with high prevalence of pre-existing medical conditions through vaccination.